(untitled) (LEARNing Landscapes, 2010)
The educational purposes of examining the revision process of a specific poem are significant and, to me, profound. It is a specialized teaching tool, one that burrows into the workings of the imagination by encouraging students to ponder specific changes to the various drafts and to discuss them. Such language talk about changes and close reading explicitly reveals those decisive steps that a poet takes in order to allow the real poem to emerge.